Mejora integral en las operaciones de una empresa de servicio de procesamiento de minerales - Guerra Galvez, Jose Manuel (2023)
The purpose of the research was to identify the most critical processes for the integral improvement of the operations of the mineral processing services company. This was supported by an external analysis using a PESTL analysis, Porter's 5 forces, Pareto diagram, among others, which served as the basis for the diagnosis of the commercial, operational, human resources and financial processes, which are distributed over nine chapters. This series of steps led to the conclusion that the main problems originate in the commercial and logistics area due to the lack of a full-time manager. It was possible to demonstrate that the lack of planning in the operational area causes economic losses and customer dissatisfaction, together with the lack of organization in the work area, as well as in the establishment of responsibilities, generating a low performance in the area. In addition, the recurrence of inadequate sources of financing was evidenced, preventing control in the areas, as well as deficiencies in the job descriptions, functions and responsibilities, due to the lack of policies and standards. Similarly, it was identified that the personnel does not have the proper training, wasting the educational levels of the workers. From the economic point of view, a positive economic NPV of S/. 837,722.87 was obtained, an IRR of 29% higher than the COK rate of 12%. The benefit-cost ratio is 1.27 with a payback time of 2.22 years. The sensitivity analysis indicates that the project is still profitable, despite all the elements that can affect the investment, it still provides an NPV and IRR higher or equal to the COK rate of 12%.